Renal failure caused by leukaemic infiltration in chronic lymphocytic leukaemia. - Phillips, J K (1993)
A case of B-CLL which was complicated by chronic renal failure due to leukaemic infiltration of the kidney is reported. Treatment with chlorambucil, prednisolone, and renal bed irradiation resulted in a substantial improvement in renal function which persisted until the the patient's death from marrow failure some eight years later. The temporal association between treatments and response suggested that renal bed radiotherapy had contributed to the improvement in renal function. This case is one of only two reported cases in which chronic renal failure due to CLL has been treated with radiotherapy. It is unique in that the renal response was shown histologically. Leukaemic infiltration of the kidney is common in CLL but, characteristically, is not associated with renal impairment. An improvement in renal function has been described in two patients with acute renal failure after chemotherapy.